GAY PRESS IN BRAZIL: a journalistic and militant look at homosexual reality in the 70s and 80s - Ferreira Silva, Carlos Humberto [UNESP] (Associacao Brasileira de Pesquisadores de Jornalismo, 2023)
This article approaches how the militancy of the homosexual movement and the journalistic practice by some agents were responsible for a unique phenomenon in the history of Brazilian journalism: the gay press. For this, a comparison was made between the subjects treated, as well as the approaches, of the newspaper Lampião da Esquina, a gay periodical that had the greatest impact between 1979 and 1981, and Folha de S.Paulo. It is a comparative document analysis, based on bibliographical research. As a result, it was possible to identify that, in addition to being unprecedented, the militant look at reality was essential for the existence of this press, making its focus not only a differential element, but a primordial one, so that the appropriate subjects were launched to the dimension of the public sphere.
PRENSA GAY EN BRASIL: una mirada periodística y militante sobre la realidad homosexual en los años 70 y 80
IMPRENSA GAY NO BRASIL: um olhar jornalístico e militante sobre a realidade homossexual nas décadas de 70 e 80
Keywords: Communication; Gay press; Homosexuality; Journalism; Militancy